2018
DOI: 10.1002/14651858.cd010512.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular revascularisation versus conservative management for intermittent claudication

Abstract: BackgroundIntermittent claudication (IC) is the classic symptomatic form of peripheral arterial disease affecting an estimated 4.5% of the general population aged 40 years and older. Patients with IC experience limitations in their ambulatory function resulting in functional disability and impaired quality of life (QoL). Endovascular revascularisation has been proposed as an effective treatment for patients with IC and is increasingly performed. ObjectivesThe main objective of this systematic review is to summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 59 publications
1
39
0
1
Order By: Relevance
“…Endovascular or open surgery may be considered for patients with IC who have severely disabling symptoms and does not respond to SET 7, 43,44 . A Cochrane review from 2018, comparing endovascular revascularization and conservative treatment for IC, concluded with a moderate effect on MWD and a large effect on PWD after 6-12 months, but no clear differences were shown between the groups after long-term follow-up 45 . Different outcome measures and study design does not allow for direct comparisons to the findings in the present study.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Endovascular or open surgery may be considered for patients with IC who have severely disabling symptoms and does not respond to SET 7, 43,44 . A Cochrane review from 2018, comparing endovascular revascularization and conservative treatment for IC, concluded with a moderate effect on MWD and a large effect on PWD after 6-12 months, but no clear differences were shown between the groups after long-term follow-up 45 . Different outcome measures and study design does not allow for direct comparisons to the findings in the present study.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…It also produces a substantial economic burden on society due to reduced working ability, hospitalisation, and associated personal and social consequences for the individual patient [12,13]. A recent Cochrane review [14] concluded that for patients with IC exercise is important regardless of whether treatment is revascularisation or overall conservative management. Supervised exercise training (SET) programmes are effective for alleviating symptoms, increasing walking distance, reducing cardiovascular risk factors and improving quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Supervised exercise training (SET) programmes are effective for alleviating symptoms, increasing walking distance, reducing cardiovascular risk factors and improving quality of life. Additionally, SET is relatively inexpensive and cost-efficient compared with other more invasive therapies [13][14][15][16]. Although evidence for SET is strong, studies exploring the effects of cross-sectoral rehabilitation intervention on patients treated for IC are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The VQ6 has acceptable to good psychometric properties regarding data quality, scale assumptions, targeting, validity and reliability. Further, VQ6 seems to be easy to use and comprehend within the target population of patients with PAD(14).The Patient Activation Measure PAM-13 is a 13 item instrument for evaluating educational interventions aimed at improving patient engagement. Patient activation specifies the level of patients' engagement and may contribute to better self-management, higher engagement in treatment and greater patient satisfaction.…”
mentioning
confidence: 99%